Analysis of electrical contact characteristics of strap contacts used in high voltage bushings under eccentric conditions - Qingyu Wang; Xiaoyu Zhou; Wei Yang; Di Hu; Shoufeng Jin; Tao Xie; Peng Liu; Zongren Peng (IET Science, Measurement & Technology)
Abstract The contact finger electrical connection structure is a crucial component of high voltage bushings, and its safety and reliability directly impact the operational stability of the bushing. To investigate electrical contact performance of the contact finger under eccentric conditions, a three‐dimensional electrical, thermal, and force multi‐physics coupling calculation model was established. Additionally, a test platform was constructed to measure electrical contact characteristics of the contact finger. The contact characteristics of the contact finger when the male head was axially deflected and radially offset compared to the female head were obtained. The research findings indicate when the male head deflects axially, the contact force changes of the contact finger blades on both sides are opposite. Moreover, as the axial deflection angle of the male head increases, the resistance of the electrical connection structure shows a rising‐slow decreasing‐fluctuating trend. The resistance is highest at 3°, with a resistance increase rate of 7.35%. Furthermore, the resistance of the electrical connection structure varies with the radial offset of the male head, following a power function. Contact failure occurs when the radial offset is 1.31 mm, and the resistance increase rate reaches 24.9% at a radial offset of 1.58 mm.